EKSPLORASI IDENTITAS DIRI DAN PERAN PADA KAKEK-NENEK SEBAGAI CAREGIVER DARI ANAK DENGAN DISABILITAS - Desiningrum, Dinie Ratri; Suryanto, Suryanto (Jurnal Psikologi, 2019)
Being grandparents is an important role and valued in the family in which family members have a certain view of the existence of grandparents in the family especially about what will be taught to their grandchildren. When grandchildren have disability, grandparents form a special expectation of themselves and grandchildren resulting on adjustment in the interaction process with grandchildren. This study aims to explore how the interaction between grandparents and grandchildren with disabilities can influence the formation of self-identity and the role of grandparents in the family. The study used a qualitative method, semi-structured interviews were conducted on 10 grandparents of children with intellectual and/or physical disabilities located in Semarang, Central Java, obtained through purposive sampling techniques. An Interpretative Phenomenology Analysis resulted in three main themes, namely: the formation of a grandfather's self-identity, the role of grandparents, and the assessment of the development of their grandchildren. The results highlight the important role of grandparents when a child has a disability, which illustrates that the grandparents' experience and role in the family vary, depending on the child's disability and the context of each family.